Pengaruh Pemberian Probiotik Lactobacillus sp. dan Bacillus sp. dengan Dosis yang Berbeda pada Media Pemeliharaan Terhadap Pertumbuhan dan Kelangsungan Hidup Udang Vaname (Litopenaeus vannamei) - Dewi, Ima Citra; Subariyanto, Subariyanto; Ernawati, Ernawati (Politeknik Negeri Sambas, 2023)
In semi-intensive aquaculture, not all the feed given can be digested by shrimp; therefore, appropriate technology, namely, the use of probiotics, is needed. This study aimed to analyze the effect of probiotics in rearing media on the growth and survival of vannamei shrimp and to identify the optimal dose. This study used a completely randomized design (CRD). The variables used were growth rate, survival, and water quality (salinity, temperature, pH, dissolved oxygen, and ammonia). Data analysis was performed using Analysis of Variance (ANOVA). Data demonstrating a significant effect were analyzed using Tukey's continuation test. The results of this study indicate that the administration of probiotics to vannamei shrimp rearing media has a significant effect on the absolute weight and daily growth rate of shrimp. Meanwhile, the survival of vannamei shrimp did not have a significant effect on their growth of vannamei shrimp. The average water quality temperatures were 25 °C in the morning and 27 °C in the afternoon. The average morning pH was 7 and the evening pH was 7, the average salinity was 30 ppt, the DO average was 5.6, and the ammonia average was 0.3. The best dose in the study was treatment C with added probiotics at a dose of 2.5 ml/l.